Stability Evaluation of Tiered Retaining Walls Supporting an Islamic Boarding School Dormitory in Solok City - Riko Zulhendra; Maulana Arif; Nabila Siti Burnama; Febiana Maulani; Febi Putri Yastari; Jeply Murdiaman Guci; Dwi Jenita Maharani (Jurnal Bangunan, Konstruksi & Desain, 2026)
This study evaluates the stability of tiered gravity retaining walls supporting an Islamic boarding school dormitory in Solok City, Indonesia. The investigation was motivated by observed ground deformation, surface erosion, and damage to structures located near the slope. Subsurface conditions were characterised using cone penetration test data from two investigation points, CPT-1 and CPT-2. The CPT results were interpreted to establish soil stratigraphy and estimate the geotechnical parameters required for numerical analysis. A two-dimensional finite element model was developed using the Mohr–Coulomb constitutive model, incorporating the existing slope geometry, soil layers, dormitory loads, groundwater conditions, and retaining wall dimensions designed in accordance with SNI 8460:2017. Slope stability was evaluated using the shear strength reduction method. The existing slope produced a factor of safety of 2.43, indicating a relatively high stability margin against deep-seated failure. After the addition of the tiered retaining walls, the factor of safety increased to 2.60, corresponding to an improvement of approximately 7%. The results indicate that the retaining walls improve stability by supporting the stepped ground and restricting lateral soil movement. However, the relatively small increase suggests that the overall response remains primarily governed by the soil properties and slope geometry. Since both calculated safety factors exceeded 2.0, the observed damage was inferred to be more closely associated with shallow surface erosion and local soil loss during rainfall rather than global slope failure. These erosion processes were not explicitly modeled and represent a limitation of the study. Effective drainage and erosion protection are therefore essential to complement the proposed retaining wall system.